2009
DOI: 10.1016/j.stem.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells and Embryonic Stem Cells Are Distinguished by Gene Expression Signatures

Abstract: SUMMARY Induced pluripotent stem cells (iPSCs) outwardly appear to be indistinguishable from embryonic stem cells (ESCs). A study of gene expression profiles of mouse and human ESCs and iPSCs suggests that, while iPSCs are quite similar to their embryonic counterparts, a recurrent gene expression signature appears in iPSCs regardless of their origin or the method by which they were generated. Upon extended culture, hiPSCs adopt a gene expression profile more similar to hESCs; however, they still retain a gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
852
3
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 918 publications
(914 citation statements)
references
References 42 publications
49
852
3
6
Order By: Relevance
“…One analysis on the whole genome scale found 71 differentially methylated regions (DMR) between three iPSC lines and three ESC lines (and 2,179 between fibroblasts and iPSC) [57]. Almost half of the DMRs show incomplete epigenetic reprogramming of the differentiated cell-of-origin genome, which is in agreement with the gene expression data [24] and epigenetic memory [58]. However, not all the DMR belong to the cell-of-origin memory, indicating that iPSC also accumulate novel aberrant epigenetic states [57,59].…”
Section: Epigenetic Comparison Between Ipsc and Escsupporting
confidence: 64%
See 3 more Smart Citations
“…One analysis on the whole genome scale found 71 differentially methylated regions (DMR) between three iPSC lines and three ESC lines (and 2,179 between fibroblasts and iPSC) [57]. Almost half of the DMRs show incomplete epigenetic reprogramming of the differentiated cell-of-origin genome, which is in agreement with the gene expression data [24] and epigenetic memory [58]. However, not all the DMR belong to the cell-of-origin memory, indicating that iPSC also accumulate novel aberrant epigenetic states [57,59].…”
Section: Epigenetic Comparison Between Ipsc and Escsupporting
confidence: 64%
“…Chin et al [24] showed that a small group of genes is continuously differentially expressed between several iPSC and ESC lines. Even though those genes couldn't be categorized by gene ontology analysis to the same functional group, they could point to iPSC as being a distinct subtype of pluripotent cells.…”
Section: Transcriptional Comparison Of Esc and Ipscmentioning
confidence: 99%
See 2 more Smart Citations
“…Pioneering work by Yamanaka and colleagues (2006) identified the first set of these dominant factors: Oct4, Sox2, Klf4, and c-Myc (OSKM). Induced pluripotent stem cells (iPSCs) obtained by transduction of these Yamanaka factors or other combinations are epigenetically and developmentally very similar, if not identical, to ESCs [8][9][10][11][12]. Although the identification of factors able to induce this reprogramming represents a major advancement, much work remains to elucidate the exact molecular mechanism underlying this direct cell reprogramming [13].…”
Section: Introductionmentioning
confidence: 99%